Application of functional magnetic resonance imaging in psychiatric clinical evaluation: Controversies and avenues. Issue 4 (13th March 2018) - Kandilarova, Sevdalina; Stoyanov, Drozdstoy; Popivanov, Ivo D.; Kostianev, Stefan
Abstract: Rationale, aims, and objectives: In this study, we have attempted to replicate the findings of altered emotional processing in depressed patients compared with healthy controls by means of functional magnetic resonance imaging during passive viewing of positive, negative, and neutral pictures from the International Affective Pictures System. Methods: Nineteen medicated depressed patients and 19 sex and age‐matched healthy controls underwent functional magnetic resonance imaging during presentation of affective pictures in a block design. The differences between the blood oxygen level dependent signal elicited in the tree conditions were compared. Within‐group and between‐group analyses were performed with stringent criteria for statistical inference ( P  < .05 with family‐wise error correction). Results: In medicated depressed patients, positive pictures compared with neutral pictures activated predominantly the posterior cingulate cortex and precuneus, as well as occipital and middle temporal areas mainly on the left side, while in healthy controls, only the occipito‐temporal areas demonstrated significant activation. The negative pictures elicited stronger activation of occipital and temporal regions in both groups and of inferior frontal gyrus only in control subjects. The difference between the groups did not reach statistical significance. Positive correlation was demonstrated between activation levels of clusters located in left precuneus/posterior cingulate cortex and left inferior/middle occipital gyrus and Montgomery‐Asberg Depression Rating Scale scores in patients while viewing positive compared with neutral pictures. Conclusions: Although the within‐group analysis demonstrated significant activations in both groups with apparent discrepancies, the between‐group analysis did not reach statistical significance under the stringent criteria for statistical inference. These results are further contextualized in the critical debate on the methodological issues of clinical evaluation in psychiatry, more specifically the validity and consistency of the applied methods and the limitations existing in the attempts to provide sound cross‐disciplinary validation of the diagnostic tools by means of neuroscience.